PENERAPAN E-GOVERNMENT MELALUI APLIKASI MY RETRIBUSI DI KABUPATEN SIDOARJO - Naailatun Nabiilah; Ilmi Usrotin Choiriyah (Halu Oleo University, 2025)
Sidoarjo Regency is making an effort to improve the quality of public services. In the current digital era, the application of information and communication technology in government administration has become an urgent need to create efficient, effective, and transparent governance. This study uses a qualitative method with a descriptive approach to examine the implementation of the My Retribution application developed by the Regional Tax and Retribution Management Agency (BPPD) of Sidoarjo Regency. Data were collected through in-depth interviews with key informants from the BPPD and the Task Force Team, field observations, and documentation studies of related policies. The results show that the My Retribution application has successfully increased the efficiency of regional retribution services by reducing administrative processes, reducing complicated bureaucracy, and increasing transparency in retribution management. This application allows the public to access retribution services online, reducing waiting times and minimising unnecessary direct contact. However, several obstacles remain in its implementation, such as limited access to technology in some communities and the need to increase socialisation of the application's use. This study concludes that the implementation of the My Retribution application is a strategic step in realising good governance through e-government, but ongoing efforts are needed to optimise its use to achieve higher quality public services that are responsive to community needs.